Application of dual-frequency EISCAT measurements to determine ion-neutral collision frequencies with the difference spectrum method - Günzkofer, Florian Ludwig; Stober, Gunter; Kero, Johan; Themens, David Russel; Miyoshi, Yasunobu; Pokhotelov, Dimitry; Borries, Claudia (2024)
The ion-neutral collision frequency affects the typical two-peak incoherent scatter spectrum. However, additional assumptions about the ion and electron temperatures are required to infer the collision frequency from incoherent scatter radar (ISR) measurements. Direct measurements of ion-neutral collision frequencies require simultaneous measurements with two ISRs at distinctly different radar frequencies. Since the collision frequency is directly correlated with the neutral particle density, such measurements are one of the very few possibilities to obtain information about the neutral atmosphere and atmosphere-ionosphere interactions in the mesosphere-lower thermosphere (MLT) region. We present the difference spectrum method to infer the vertical profile of the ion-neutral collision frequency across the MLT region. Other than using a simultaneous fit of the two spectra with a combined error function, the differences spectrum method can be based on standard ISR analysis software, i.e. GUISDAP, and therefore, is more widely applicable. We present ion-neutral collision frequency profiles obtained from several combined EISCAT UHF and VHF campaigns, utilizing manda and beata pulse codes. We demonstrate that the collision frequency can significantly deviate from climatological profiles inferred from empirical models such as NRLMSIS. The impact of auroral particle precipitation on the neutral atmosphere density and, thus, the ion-neutral collision frequency is shown as well. Dual-frequency EISCAT campaigns were conducted around the fall and spring equinoxes in the same measurement mode to investigate seasonal variations of the collision frequency profiles.